2008
DOI: 10.1007/s11079-008-9092-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Migration and Foreign Direct Investment

Abstract: The question of complementarity or substitutability of FDI and international labour mobility has not yet been answered. The substitutability assumption does not take into consideration the technological spillover of FDI in the host countries. Moreover, migration flows reveal cultural characteristics and labour force properties of their native country which may stimulate bilateral business networks, strengthening the complementarity assumption between capital and labour flows. In this paper we build a continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In contrast, the relationship between migration and FDI is an under-investigated area. A limited number of studies for example, Aroca and Maloney (2005), Tong (2005), Buch et al (2006), Kugler and Rapoport (2007), Bhattacharya and Groznik (2008), Javorcik et al (2010) and Federici and Giannetti (2010) have addressed this link, and they reported a positive and significant link between migration and FDI. Javorcik et al (2010) have shown that the stock of US FDI abroad is positively correlated with the presence of migrants.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the relationship between migration and FDI is an under-investigated area. A limited number of studies for example, Aroca and Maloney (2005), Tong (2005), Buch et al (2006), Kugler and Rapoport (2007), Bhattacharya and Groznik (2008), Javorcik et al (2010) and Federici and Giannetti (2010) have addressed this link, and they reported a positive and significant link between migration and FDI. Javorcik et al (2010) have shown that the stock of US FDI abroad is positively correlated with the presence of migrants.…”
Section: Introductionmentioning
confidence: 99%
“…This explanation does not confront with that of D'Agosto et al (2006) which claim that FDI increases bilateral information and knowledge on employment, wages abroad, and practices, technical and organizational procedures in foreign enterprises. Neither does it demur to Federici and Giannetti (2008) which claim that migration flows reveal cultural characteristics and labour force features that may stimulate inflows of capital to the emigrants' homelands.…”
Section: è2mentioning
confidence: 99%
“…This paper builds upon the literature on the impacts of temporary and permanent migration on economic performance in source countries. Recent contributions along these lines include Dustmann, Fadlon, and Weiss (), Federici and Giannetti (), and Ahmed and Walmsley (). Dustmann, Fadlon, and Weiss () present a model showing that return migration can lead to a mitigation of the brain drain, or even the creation of a “brain gain,” where those who return bring back to the home country augmented local skills .…”
Section: Introductionmentioning
confidence: 99%
“…Dustmann, Fadlon, and Weiss () present a model showing that return migration can lead to a mitigation of the brain drain, or even the creation of a “brain gain,” where those who return bring back to the home country augmented local skills . Federici and Giannetti () find that temporary migrant workers stimulate foreign direct investments’ inflows in their origin countries. Using a computational general equilibrium (CGE) model, Ahmed and Walmsley () find positive effects of increased temporary migration from India on its economy.…”
Section: Introductionmentioning
confidence: 99%